Guide to giving during the COVID-19 pandemic: the moderating role of religious belief on donor attitude. Issue 1 (5th December 2020) - Sarea, Adel; Bin-Nashwan, Saeed Awadh
Abstract : Purpose: This study aims to empirically explore donors' responses to fundraising appeals to mitigate the socio-economic impact of the COVID-19 crisis. Some governments worldwide have launched fundraising campaigns to support the pandemic relief efforts, such as the Feena Khair* campaign in the Kingdom of Bahrain. Specifically, the study examines how the internal and external aspects can fuel beliefs in the inclination of donors to give money. Design/methodology/approach: A quantitative survey instrument was developed, validated and disseminated. A total of 263 usable responses were obtained using the snowballing sampling technique. Partial least squares-structural equation modeling was used to analyze the research model and obtain meaningful results. Findings: The results show that external aspects, i.e. charity projects and trust in charities, have a significant relationship with donors' attitudes toward fundraising appeal for the COVID-19 fight. Interestingly, the study demonstrates a significant moderating effect of internal values of religious beliefs on the positive relationship between external aspects and attitude to give money. Practical implications: The results suggest that governments and non-profit organizations should consider the important role of religious beliefs in driving people's attitudes to engage in fundraising appeals to fight the pandemic. These findings could generate better insights and policies that boost relief and donation efforts in many ways, such as embarking on sensitization programs to create sufficient awareness on the importance of giving and social solidarity during this challenging time, strengthening the religious faith of donors, setting up charity projects with inclusive information and nurturing a high level of public confidence in charities. Originality/value: This study is likely the first study to focus on fundraising campaign attitudes during the COVID-19 pandemic in Bahrain. It is a pioneer study scrutinizing the moderating effect of religious beliefs on the association between extrinsic perspectives of donors and their attitudes toward monetary donations.